Change of the guards—Looking back at Michael Droller: Visionary and supporter—The perspective of the International Bladder Cancer Network - Schmitz-Dräger, Bernd; Grossmann, H. Barton; Goebell, Peter; Kamat, Ashish M.; Black, Peter C. (Urologic Oncology-Seminars and Original Investigations, 2025)
Objective: Professor Michael Droller is stepping down as Editor-in-chief of Urologic Oncology: Seminars and Original Investigations, a journal that he co-founded. This manuscript describes his relation with the International Bladder Cancer Network (IBCN) and reviews his impact on the development of this association. Material and Methods: Reviewing its 25-year long history, the IBCN reconsiders Michael Droller´s relevance for the unexpected development of the association and highlights his contributions. Results: The IBCN gratefully acknowledges the invaluable support of Michael Droller in its goal to foster interdisciplinary collaboration among scientists dedicated to advancing the diagnosis and treatment of bladder cancer, and to cultivate the next generation of researchers in this field. Conclusions: Michael Droller's legacy within the IBCN is profound. His guidance, critical insights, and unwavering commitment have been pivotal in establishing the network as a leading force in bladder cancer research.
CRIS-Team Scopus Importer:2025-02-28
Keywords: bladder cancer; diagnosis; International Bladder Cancer Network; Michael Droller; molecular markers; multidisciplinary; therapy